PENGARUH PENGETAHUAN INVESTASI DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI PADA NASABAH BANK JATIM JEMBER DENGAN INKLUSI KEUANGAN SEBAGAI VARIABEL INTERVENING - Bastarani, Penny Siska; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
The research objective is to determine the effect of investment knowledge and financial literacy on investment decisions for customers of Bank Jatim Jember with financial inclusion as an Intervening variable. Abdurachman Saleh University, Situbondo. The sampling technique used in this study was simple random sampling using the Slovin formula with a tolerable error rate of 10% for 96 customers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM)The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that investment knowledge has a positive and significant effect on financial inclusion, financial literacy has a positive and significant effect on financial inclusion, investment knowledge has a positive and significant effect on investment decisions, financial literacy has a negative and insignificant effect on investment decisions, financial inclusion has a positive and significant effect on investment decisions, investment knowledge has a positive and significant effect on investment decisions through financial inclusion, financial literacy has a positive and significant effect on investment decisions through financial inclusion.